Less is more : minimalism in fashion - Walker, Harriet (London : Merrell, 2011)
Includes fashion designs by Haider Ackermann, Azzedine Alaïa, Matthew Ames, Hardy Amies, Giorgio Armani, Cristo?bal Balenciaga, Victoria Beckham, Geoffrey Beene, Marc Bohan, Pierre Cardin, Hattie Carnegie, Céline, Cerruti, Hussein Chalayan, Coco Chanel, Chloé, COS, Comme des Garcons and others.
boek